Effect of coating material on the electrical characteristics of porcelain insulator - Roslan, Muhammad Hafizzuddin; Othman, Nordiana Azlin; Mohd Jamail, Nor Akmal; Ismail, Muhammad Nafis; Baharom, Md Nor Ramdon (Penerbit UTHM, 2020)
The nature of overhead porcelain insulators that mounted and exposed to environment may prompt the deposition of contamination sources on its surface. The contaminated insulator especially in wet condition may threaten the reliability of power system network. Thus by coating the insulator with coating material, it is believed to reduce the charge distribution [1]. However, the coating materials on insulator string are different in their behavior. Coatings are used to reduce surface discharges, surface leakage current, space charge accumulation as well as flashover occurrence on existing and installed porcelain insulators.